Community, capabilities, and the social entrepreneurship ecosystem. (4th May 2023) - Warnecke, Tonia; Balzac-Arroyo, Josephine
ABSTRACT: Social entrepreneurs do not work alone; they shape and are shaped by their entrepreneurial ecosystem. While navigating the ecosystem, it is critical to remain focused on the community, including beneficiaries and the end-user. After a brief review of the entrepreneurship ecosystem (EE) and social entrepreneurship ecosystem (SEE) literature and its evolution over time, we elaborate the active and passive roles of community within the SEE, considering both agency and participation. Turning to the capabilities approach, developed by Amartya Sen and Martha Nussbaum, we show its relevance not only for understanding the way community impacts the SEE, but also as a theoretical frame for processes and programs that aim to further embed community in the SEE. To illustrate this, we discuss the processes of asset mapping, human-centered design, and integrated advocacy; the way they relate to strengthening community-SEE integration; and the way they reflect the capabilities approach. We conclude by discussing lessons learned and providing suggestions for further research.